PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nola Veronica Lestari; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The study aims to determine the effect of capital structure on profitability in the pharmaceutical sector manufacturing companies listed on the indonesian stock exchange. Capital structure ratios used Debt to Equity Ratio (DER), Debt to Total Assets Ratio (DR) and profitability ratio used Return On Invesment (ROI), Return On Equity (ROE). The method used to determine the effect of capital structure on profitability using sample linear refresh.Data used in this research in secondary data, financial reports. The recorded data in indonesian stock exchange during the 5 years 2010 to 2014. The dark, population in this were 8 companies. Data analysis using simple linear regression analysis, test f, and the coefficient of determination test. Data analysis using SPSS 21.Analysis shows the capital structure affect the profitability of the pharmaceutical sector manufacturing companies listed on the indonesian stock exchange. Simultaneous research results show the influence of capital structure on profitability in the pharmaceutical sector manufacturing companies listed on the indonesian stock exchange.Key words : Debt to Equity Ratio (DER), Debt to Total Assets Ratio (DR), Return On Invesment (ROI) and Return On Equity (ROE)